From Landlocked to Land-Linked : Unlocking the Potential of Lao-China Rail Connectivity - World Bank (World Bank, Vientiane, 2020)
The Lao-China railway (also known as the Boten-Vientiane railway) is part of six international economic corridors under China’s belt and road initiative (BRI). As part of the BRI, the Vientiane-Boten railway connects Lao Peoples Democratic Republic (PDR) with not only China (and eventually Singapore) but also the entire BRI network. The railway section that connects Kunming in China with Vientiane in Lao PDR is under construction, with plans to build a railway terminal close to export processing zones (EPZs) and the logistics park in Vientiane. The Thai railway section is designed to carry passenger trains on a new high-speed network while moving cargo traffic to the old meter-gauge network, creating potential challenges for transloading goods and passengers. The Lao-China railway aims to create closer trade linkages between not only Lao PDR and China but also between all economies in the BRI, which is expected to lower trade costs and accelerate economic growth and poverty reduction in the region. To fully benefit from the railway investment, Lao PDR needs to develop efficient services and production along the railway corridor to outcompete maritime transport in terms of cost and time. Increased domestic and foreign private-sector investment will also require early information sharing with the private sector regarding planned railway operations. Policymakers need to adopt key policy reforms and build complementary infrastructure to connect production areas to the railway network. This study identifies key investments and policy reforms to maximize the benefits of the Vientiane-Boten railway for Lao PDR, demonstrating the complementarity of hard and soft infrastructure investments.